Formulação coagulante de Moringa oleifera e sulfato de alumínio associada à capsula porosa de argila para tratamento de água de piscina - Ribeiro, Thaís (2022)
The study proposed to obtain an alternative treatment for the clarification of swimming pool water in order to reduce the concentration of aluminum sulfate used in this process. The proposed coagulant formulation was based on the association of salt with the protein extracted from the seed of Moringa oleifera. Initially, the seed of Moringa oleifera was manipulated obtaining different solutions: protein (1g.L-1 ) and oil (1mL.L-1 ) extracted via Soxhlet, liquid saline solution (1g.L-1 ) and lyophilized (1g.L-1 ). The formulations were submitted to JarTest monitoring pH and turbidity. The lyophilized saline solution was statistically more efficient, reducing 87% of the turbidity and maintaining the pH in the range established by NBR 10.818. Subsequently, the lyophilized solution was associated with aluminum sulfate in the proportions 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7 and 0:10 and subjected them to the Jar-Test. In the end, the 3:7 ratio was the most efficient, not altering the pH and reducing turbidity by 98%, an efficiency statistically equal to that measured using only aluminum sulfate (99%). At the same time, the porous slip capsule was obtained, the formulation was added inside it in a 3:7 proportion and the whole was subjected to water treatment with a turbidity of 100 NTU. In this step, it was found that the capsule kept on the surface, containing both the powdered and diluted formulations, reduces the turbidity by 98%, a percentage statistically higher than the same coagulant treatment, but without the aid of the capsule. Once the ideal coagulant formulation was obtained (3:7) and the efficiency of the capsule was proven, the treatments were applied in 30 L of water with a turbidity of 100 NTU, testing, at this stage, the agitation condition. Turbidity, electrical conductivity, pH, total alkalinity and total hardness were monitored. All treatments obtained results statistically superior to the control test. The pH, total hardness and total alkalinity did not suffer significant changes caused by the treatments. The electrical conductivity corresponded to approximately 550 µS.cm-1 in the treatments tested in an inert medium and to 450 µS.cm-1 under agitation. In an inert medium, turbidity was reduced by 91% (powder) and 89% (diluted), and under agitation, removals of 96% (powder) and 91% (diluted) were achieved. Except for the formulation diluted in an inert medium, all treatments were considered statistically equal. Thus, it was found that the formulation obtained by associating Moringa oleifera with aluminum sulfate in the proportion 3:7 inserted in a porous slipper capsule is efficient in the clarification of swimming pool water, reducing the use of salt by up to 30% without compromising the efficiency in clarification. Furthermore, it was verified the importance of agitation when applying the treatments, since better results were obtained in this scenario.